Does the Fixed Oil from the Pequi Fruit Extracted by Extractivists from Chapada of Araripe have an Antibacterial Effect?. Issue 1 (2022) - Landim, Hemerson Soares; Correia, Dennis Bezerra; Pereira, Raimundo Luiz Silva; Rocha, Janaína Esmeraldo; Costa, José Galberto Martins da
No abstract available